EFEKTIVITAS APLIKASI SISTEM INFORMASI PELAYANAN KEPEGAWAIAN (SINAGA) PADA BADAN KEPEGAWAIAN DAERAH PROVINSI JAWA TENGAH - Ayu Ambar Wati; Hardi Warsono (Journal of Management and Public Policy, 2026)
The Regional Civil Service Agency (BKD) of Central Java Province is trying to implement an administrative system that is integrated with information technology. The concrete implementation of these efforts is the launch of the Personnel Services Information System Application (SINAGA) as a form of digital breakthrough in personnel services. The implementation of personnel services through the SINAGA Application is still not optimal. This is because there are still problems experienced by users, such as technical problems and server problems that often go down. This research aims to analyze the effectiveness of the SINAGA Application and the factors driving and inhibiting its effectiveness. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation. This research uses effectiveness theory according to Tangkilisan (2005), namely target achievement, adaptability, job satisfaction, and responsibility, and uses the theory of driving and inhibiting factors that influence effectiveness according to Najidah (2019), namely planning, coordination, and accuracy of service. The research results show that the effectiveness of staffing services through the SINAGA Application is not yet optimal, this is because not all staffing services are available, limited annual budgets for updating the application, technical obstacles, and user discipline in following the guidelines in operating the application. Driving factors include the SINAGA Application contributing positively to efficiency, data accuracy and transparency in personnel services. The inhibiting factors found included misperceptions and lack of coordination between fields in BKD, as well as technical obstacles originating from external application factors. In order to improve the quality of SINAGA, the Regional Civil Service Agency (BKD) of Central Java Province needs to develop SINAGA in stages, as well as optimize infrastructure and server capacity to minimize the possibility of technical problems arising.